Rehabilitation of atrophic jaw using iliac onlay bone graft combined with dental implants - Truc Thi Hoang Nguyen; Mi Young Eo; Tae Seong Kuk; Hoon Myoung; Soung Min Kim (SpringerOpen, 2019)
Abstract Background Rehabilitating severely atrophic alveolar crests remains challenging for implantologists and maxillofacial surgeons. Recently, a combination of augmentation and dental implantation has been used to treat cases with severe bone atrophy in the maxilla and mandible. Among autogenous bone grafts, iliac bone grafting (IBG) is considered safe for collecting large amounts of bone and obtaining high-density multipotent cells. However, vertical bone resorption may occur during the initial healing stage after IBG. The purpose of the present study is to evaluate bone graft success and implant survival rate, along with bone height in the augmented site and marginal bone level around dental implants placed in iliac onlay bone grafts. We also introduce technique and treatment considerations for successful IBG procedures, as well as optimal implant installation strategy and soft tissue manipulation. Methods We examined seven patients who were treated with IBG combined with implant systems over a period of 10 years. The long-term success rate of bone grafts and implant survival rate were recorded. Bone height change and marginal bone loss (MBL) were analyzed by assessing the radiograms acquired after augmentation, at implant installation, prosthetic loading, and after installation 1 year, 2 years, 3 years, and 5 years. Results In a mean observation period of 50 months (range 12-62 months), the success rate of IBG was 100%. A total of 29 implants were installed and the implant success rate was 100%. The mean bone height reductions compared to post-augmentation bone heights were 1.33 ± 0.81 mm after 3 months, 2.00 ± 1.88 mm at implant installation, 2.55 ± 1.68 mm at prosthetic loading, and 3.05 ± 1.63 mm after implant installation 1 year. The cumulative bone height change after implant installation 5 years was 4.05 ± 1.83 mm which corresponds to a mean resorption rate of 42.5%. The mean MBL after installation 3 months, at prosthetic loading, and after installation 1 year, 2 years, 3 years, and 5 years follow-ups were significantly higher than at implant installation. However, MBL at 2 years, 3 years, and 5 years post-installation did not differ significantly (p < 0.05). Conclusion In patients with atrophic jaws, a combination of the iliac onlay bone graft and dental implants can result in satisfactory reconstruction and reliable long-term prognosis. Despite early stage vertical bone resorption, we observed high success rates and comparable MBL over long-term follow-up. To reduce bone resorption, case evaluation and surgical planning must be meticulous. Further large-scale studies with longer-term follow-up are needed.